The Social Backgrounds, Dharma Lineages, and Achievements of Women Chan Masters, 1572–1722 - Chen, Yuh-Neu (Religions, 2023)
This article continues the investigation of my previous paper ‘Wan Ming Qing chu dongnan yanhai gangkou Fosi de biqiuni shenying’ 晚明清初東南沿海港口佛寺的比丘尼身影 (‘The Historic Image of the Bhikkhuni Who Lived at Buddhist Monasteries of Seaport Cities of Southeast China during the Late Ming and Early Qing Period’). While discussing the space of port city Buddhist monasteries and their urban environment, and how they aided or hindered the bhikkhuni monastic community, or individual bhikkhuni in their practice, life, and personal achievements, I also realized that a bhikkhuni’s family background and her connections with local gentry and eminent persons indeed contributed to the rise of her prestige. The publication and distribution of the recorded sayings of several women Chan monastics residing in the Buddhist monasteries of port cities during the late Ming and early Qing periods can be regarded as a commendable breakthrough in the Buddhist history of this period. To further clarify the resource structure that helped support these Chan bhikkhuni, including the multifaceted interplay between their blood ties, dharma connections, and regional connections, I aim here to particularly examine the backgrounds, dharma lineages, activity regions, and ultimate achievements of these women Chan monastics. I will consider how it is that these Chan bhikkhuni were able to use such resources to achieve the distinction of having their deeds recorded, while so many more of their fellow bhikkhuni have been forgotten. While in real life, there were a rather large number of bhikkhuni, only a few have been able to have their names passed down to posterity. Women have always faced greater challenges than men in having their voices known and receiving social recognition, and even for men, this has never been easy without a relevant support system—one’s own personal cultivation, the prestige of one’s family, the power of one’s dharma lineage, the strength of one’s personal connection, the disparity in the resources that one has access to in their urban or rural society, etc.; all these various factors affect one’s achievements and performance. Especially in Chan Buddhist texts, where women are greatly underrepresented, I aim to explore in this paper how a women Chan monastic could be included in the Chan historical record, have her recorded sayings published, and have a place in Buddhism or the dharma lineages of Chan.